Parametric stress analysis of steel multiplanar tubular XT- and XX- joints - Wu, Nai Wen. (2008)
In this project, large-scale steel tubular XT and XX-joints are designed following current industrial practices. The steel XT-joint specimen is tested under 11 basic axial and axial combined with In-Plane-Bending (IPB) and Out-of-Plane-Bending (OPB) load cases. The XX-joint specimen is tested under 12 basic and combined loads. The SCFs, strain concentration factors (SNCFs) and the SCF to SNCF ratios (S/N Ratios) at typical crown and saddle hot spot locations are investigated.